Oxygen enhancement ratios of cancer cells after exposure to intensity modulated x-ray fields: DNA damage and cell survival. (6th April 2021) - Matsuya, Yusuke; McMahon, Stephen J; Butterworth, Karl T; Naijo, Shingo; Nara, Isshi; Yachi, Yoshie; Saga, Ryo; Ishikawa, Masayori; Sato, Tatsuhiko; Date, Hiroyuki; Prise, Kevin M
Abstract: Hypoxic cancer cells within solid tumours show radio-resistance, leading to malignant progression in fractionated radiotherapy. When prescribing dose to tumours under heterogeneous oxygen pressure with intensity-modulated radiation fields, intercellular signalling could have an impact on radiosensitivity between in-field and out-of-field (OF) cells. However, the impact of hypoxia on radio-sensitivity under modulated radiation intensity remains to be fully clarified. Here, we investigate the impact of hypoxia on in-field and OF radio-sensitivities using two types of cancer cells, DU145 and H1299. Using a nBIONIX hypoxic culture kit and a shielding technique to irradiate 50% of a cell culture flask, oxygen enhancement ratios for double-strand breaks (DSB) and cell death endpoints were determined. These in vitro measurements indicate that hypoxia impacts OF cells, although the hypoxic impacts on OF cells for cell survival were dose-dependent and smaller compared to those for in-field and uniformly irradiated cells. These decreased radio-sensitivities of OF cells were shown as a consistent tendency for both DSB and cell death endpoints, suggesting that radiation-induced intercellular communication is of importance in advanced radiotherapy dose-distributions such as with intensity-modulated radiotherapy.